Analisis Kinerja Badan Layanan Umum Di Perguruan Tinggi (Studi Kasus di IAIN Sulthan Thaha Saifuddin Jambi Tahun 2010-2012) - Lestiyani, Tri Endah Karya; Suranto, Suranto (Universitas Muhammadiyah Yogyakarta, 2015)
Indonesian constitution no. 1 year of 2004 about the state treasury that can open the new corridor for the performance-based budgeting application in government circumtances. The article 68 and article 69 of the constitutionsassert that the government instance have the main duty and function to serves the public society. It also able to applythe flexible budgeting managent pattern by accentuated the productivity, efficiency, and effectivity in a form of thePublic Services agency (BLU). BLU is expected as the real image of performance-based budgeting managementapplication. IAIN Sulthan Thaha Saifuddin has been a BLU since November 23rd 2009. In performance of BLU, IAINSulthan Thaha Saifuddin experiences the change of budgeting systems, Organization structure, and organizationperformance achievement. This research tried to know the evaluation of BLU in IAIN STS by using Balanced Scorecard.The Application of BSC based on 4 perspectives, encompases the monetary perspectives, consumer perspectives,internal bussiness perspectives,and learning and developing perspectives. The evaluation of BLU is proposed toknow the effort of public services quality improvement, transparancy and accountability of government budget managementin IAIN Sulthan Thaha Saifuddin. The approach of this research is qualitative describtive and the methodealso use the qualitative methode. While, the data collecting use the questionaire to the BLU group-based respondents.The result of the research shows the work of Public Service Agency in IAIN Sultan Thaha Saifuddin Jambi is alreadywork effectively but it still need to be improved, especially the implementation of Standard Operational Procedure(SOP) and the minimal standard of services / Standar Pelayanan Minimal (SPM) in order to expected to be prominentconcrete examples of the application of financial management based on the results (performance).